2017
DOI: 10.1016/j.solener.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Energy analysis and shadow modeling of a rectangular type salt gradient solar pond

Abstract: This is a repository copy of Energy analysis and shadow modeling of a rectangular type salt gradient solar pond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…For each structure type an experimental study has been chosen from the literature. Moreover, a modeling method presented in the literature has been modified with the presented relations for the sunny areas . By employing the modified method, for all the configurations, the temperature of the LCZ layer has been calculated theoretically.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each structure type an experimental study has been chosen from the literature. Moreover, a modeling method presented in the literature has been modified with the presented relations for the sunny areas . By employing the modified method, for all the configurations, the temperature of the LCZ layer has been calculated theoretically.…”
Section: Resultsmentioning
confidence: 99%
“…Before investigating the results, the presented modifications must be validated. For each structure type an experimental study [21]. By employing the modified method, for all the configurations, the temperature of the LCZ layer has been calculated theoretically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aramesh et al worked on the energy analysis of the shadow modeling of a rectangular version solar pond (SP). It was utilized to determine the performance of the SP by modifying known equations, and it was concluded that these equations were more compatible with the experimental data . The ETSC is a simple water heating system that can convert solar energy into heat.…”
Section: Introductionmentioning
confidence: 99%
“…It was utilized to determine the performance of the SP by modifying known equations, and it was concluded that these equations were more compatible with the experimental data. 10 The ETSC is a simple water heating system that can convert solar energy into heat. The ETSC system can be used for many purposes such as domestic and commercial hot water, space heating, pool heating, and floor heating.…”
Section: Introductionmentioning
confidence: 99%